Resolva os sistemas utilizando o método da substituição
Anexos:
![](https://pt-static.z-dn.net/files/da4/5f6aa396ba0b14d89c834d11359868df.jpg)
![](https://pt-static.z-dn.net/files/d2f/2f1231e0d678ff6f5d6148d4464b6679.jpg)
Soluções para a tarefa
Respondido por
4
b) m -3n= 2
4m +2n= -1
m -3n= 2 *(-2)
4m+2n= -1 *(3)
-2m + 6n = -4
12m+6n = -3
10m + 0n = -7
10m = -7
m= -7/10
substituindo :
-7/10 - 3n = 2
-7/10 + 2 = 3n
-7 /10 + 20/10= 13/10 = +3n
13/10 = 3n
3n*10=3
30n=13
n=13/30
c) 3p + q = -2
2p -5q = 3
3p + q -2 *(5)
2p - 5q = 3
15p - 5 q = -10
2p-5q= 3
17p=-7
p=-7/17
substituindo:
-7/17 +q = -2
-7/17 +34/17 = +27/17 = -q
(-1) -q = 27/17
q= -27/17
4m +2n= -1
m -3n= 2 *(-2)
4m+2n= -1 *(3)
-2m + 6n = -4
12m+6n = -3
10m + 0n = -7
10m = -7
m= -7/10
substituindo :
-7/10 - 3n = 2
-7/10 + 2 = 3n
-7 /10 + 20/10= 13/10 = +3n
13/10 = 3n
3n*10=3
30n=13
n=13/30
c) 3p + q = -2
2p -5q = 3
3p + q -2 *(5)
2p - 5q = 3
15p - 5 q = -10
2p-5q= 3
17p=-7
p=-7/17
substituindo:
-7/17 +q = -2
-7/17 +34/17 = +27/17 = -q
(-1) -q = 27/17
q= -27/17
Perguntas interessantes